Obesitas dan Sindrom Metabolik pada Pasien Medical Check Up, Siloam Hospitals Lippo-Karawaci - Wahyu, Indriyani; Prasetyaningsih, Ani; Ngadiarti, Iskari (Lembaga Penerbitan Unversitas Esa Unggul, 2011)
AbstractMetabolic syndrome is a collection of complaints and symptoms based on the presence of insulin resistance. The main factor which can cause insulin became resistance is obesity. The aims of this study was to understand the relationship between obesity and the metabolic syndrome indicators in patients undergoing medical check-up, Siloam Hospitals Lippo Karawaci. This study is associative with cross-sectional design. The total of population are patients who are obese at the medical check up of Siloam Hospitals Lippo Karawaci. Whereas, the total of sample are 50 people were patients with a BMI > 25 with the inclusive criteria, age above 35 years, had never been diagnosed the disease associated with the metabolic syndrome and had never received the treatment. We used Correlation- Regression Test. The results shows that the majority of male respondents (82 %), mean age (44.6 ±7.07). From the data, most of respondents did not smoke (66 %). The bivariate test results shows there is significant relationship between BMI and blood triglyceride levels and waist circumference (P <0.05), but no significant relationship between BMI and fasting blood sugar levels, HDL cholesterol levels and blood pressure (P≥0.05). We found also, there is no significant association between dietary intake and BMI of the respondents (P≥0.05). BMI is an important indicator of the level of blood triglycerides and waist circumference. Key Words: Obesity, Metabolic Syndrome, BMI AbstrakSindrom metabolik adalah sekumpulan keluhan dan gejala yang didasari oleh adanya resistensi insulin. Faktor penyebab resistensi insulin antara lain obesitas. Penelitian ini bertujuan mempelajari hubungan antara obesitas dan indikator-indikator sindrom metabolik pada pasien yang melakukan medical check up di Siloam Hospitals Lippo Karawaci. Jenis penelitian ini bersifat assosiatif dengan pendekatan cross sectional. Populasinya adalah semua pasien yang obesitas di bagian medical check up Siloam Hospitals Lippo Karawaci. Sedangkan sampelnya sebanyak 50 orang adalah pasien dengan BMI > 25 dengan inclusive kriteria, usia di atas 35 tahun, belum pernah didiagnosa suatu penyakit yang berhubungan dengan sindrom metabolik dan belum pernah mendapatkan pengobatan. Uji yang digunakan Uji Korelasi. Berdasarkan hasil didapat bahwa sebagian besar responden pria ( 82 %), rata-rata usia 44,6 + 7.07. Dari seluruh responden, sebagian besar (66 %) responden tidak merokok. Hasil uji statistik menunjukkan ada hubungan yang bermakna antara BMI dan kadar trigliserida darah dan ukuran lingkar pinggang (p< 0.05); namun tidak ada hubungan yang bermakna antara BMI dan kadar gula darah puasa, kadar HDL dan tekanan darah. Juga tidak ada hubungan yang bermakna antara asupan makanan dan BMI responden. BMI merupakan indikator penting tingkat trigliserida darah dan ukuran lingkar pinggang. Kata Kunci: Obesitas, Sindrom Metabolik, BMI